2004
DOI: 10.1161/01.hyp.0000121882.42731.6b
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donor Sodium Nitroprusside Dilates Rat Small Arteries by Activation of Inward Rectifier Potassium Channels

Abstract: Abstract-The role of vascular smooth muscle inward rectifier K ϩ (K IR ) channels in the mechanisms underlying vasodilation is still unclear. The hypothesis that K IR channels are involved in sodium nitroprusside (SNP)-induced dilation of rat-tail small arteries was tested. SNP relaxed tail small arteries with an EC 50 of 2.6ϫ10Ϫ8 mol/L. Endothelium removal did not attenuate this effect. Vessel pretreatment with hydroxocobalamin, a nitric oxide (NO) scavenger, but not with rhodanese and sodium thiosulfate, ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 42 publications
8
46
0
1
Order By: Relevance
“…It suggests that the vasorelaxation effect of FLNT is mediated by NO. This finding is in agreement with previous reports showing that the vasorelaxation induced by nitrate involves NO production (25,36). In contrast, we found that nicorandil still retained most of its ability to cause relaxation of the rat aorta artery in the presence of hydroxocobalamin, which suggests that NO is not a primary factor for the nicorandil relaxation in rat aorta artery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It suggests that the vasorelaxation effect of FLNT is mediated by NO. This finding is in agreement with previous reports showing that the vasorelaxation induced by nitrate involves NO production (25,36). In contrast, we found that nicorandil still retained most of its ability to cause relaxation of the rat aorta artery in the presence of hydroxocobalamin, which suggests that NO is not a primary factor for the nicorandil relaxation in rat aorta artery.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that NO donor or nitrate activated K Ca channels directly (36) or through increasing the activity of cGMP-dependent protein kinase (3,37). Another study showed that a NO donor could activate K IR by increasing the K IR current (25).…”
Section: Discussionmentioning
confidence: 99%
“…Schubert et al (33) observed that the relaxation induced by SNP in rat tail small arteries was less potent in the presence of barium, a selective KIR blocker. In addition, SNP increased the amplitude of the KIR current, and this effect was almost abolished in the presence of barium, indicating that KIR participates in the SNP-induced relaxation.…”
Section: Hypertension and Endothelial Dysfunctionmentioning
confidence: 99%
“…This indicates those kirs channels involve are in the smooth muscle relaxation via cell membrane hyperpolarization (Schubert et al, 2004). Moreover, the vasoconstrictor effect of BaCl2 due to a fact that BaCl2 interfere with BK potentiated EDHF vasodilatory mechanism.…”
Section: Discussionmentioning
confidence: 91%